Cephalometric evaluation of the therapeutic effects of the Herbst appliance in the treatment of Class II. Div I. malocclusion - (:unkn) unknown (My University, 1992)
The purpose of this investigation was to assess the therapeutic effects of the Herbst appliance cephalometrically. Twenty patients were chosen from our clinical intake. Care was taken to select patients who had Class II Div I malocclusion and horizontal growth pattern. Skeletal age was the main selection criterion. Patients in the peak growth period were chosen. A Herbst appliance was used on the first ten patients. The other ten patients served as controls. Standardized profile roentgenograms were taken initially and at the end of a six month observation period. The following results were obtained: 1. Normal occlusal conditions occurred. 2. The mandible was positioned anteriorly and lengthened due to the Herbst therapy. 3. The most significant effect on the maxilla was the decrease in the 1- SN angle and in overjet reduction.
Keywords: Female; Humans; Treatment Outcome; Male; Child; Reference Values; Malocclusion, Angle Class II; Cephalometry; Evaluation Studies as Topic; Orthodontic Appliances, Functional